1997
DOI: 10.1177/0146167297237003
|View full text |Cite
|
Sign up to set email alerts
|

Social Ostracism by Coworkers: Does Rejection Lead to Loafing or Compensation?

Abstract: A new theoretical model and research paradigm are introduced to investigate the phenomenon of social ostracism-being ignored by others who are in one's presence. The authors examined the effects of social ostracism on individuals' subsequent contributions to a group task. Social loafing Optically occurs on collective tasks. However; to regain their sense of belonging to the group, the authors expected ostracized individuals to socially compensate-to work harder collectively than coactively. Participants were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
457
6
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 558 publications
(492 citation statements)
references
References 43 publications
20
457
6
9
Order By: Relevance
“…These results are consistent with those of K. D. Williams, Cheung, and Choi (2000), who found greater conformity among ostracized individuals. However, they are inconsistent with the results of K. D. Williams and Sommer (1997), who found that ostracized women worked harder on a subsequent group task. Future research should determine which rejection and ostracism situations lead to passivity and which do not.…”
Section: Findings Consistent With the Deconstructed Statecontrasting
confidence: 96%
“…These results are consistent with those of K. D. Williams, Cheung, and Choi (2000), who found greater conformity among ostracized individuals. However, they are inconsistent with the results of K. D. Williams and Sommer (1997), who found that ostracized women worked harder on a subsequent group task. Future research should determine which rejection and ostracism situations lead to passivity and which do not.…”
Section: Findings Consistent With the Deconstructed Statecontrasting
confidence: 96%
“…For instance, Williams and Sommers (1997) found that women responded to rejection from a group by working harder on a subsequent collective task. In a similar vein, Gardner, Pickett, and…”
Section: Studymentioning
confidence: 99%
“…Although social interaction is engaging for both males and females, it is most likely to be considered a motivated performance for females as the latter are often more sensitive to interpersonal feedback (e.g., Williams and Sommer 1997). Of these 90 participants, 30 were selected for nonverbal analysis on the basis of their cardiovascular patterns (see section ''Selection of Target Participants'').…”
Section: Participantsmentioning
confidence: 99%